Short-term response of soil N-cycling genes and transcripts to fertilization with nitrification and urease inhibitors, and relationship with field-scale N2O emissions. (March 2020) - Tosi, Micaela; Brown, Shannon; Ferrari Machado, Pedro Vitor; Wagner-Riddle, Claudia; Dunfield, Kari
Abstract: In agroecosystems, efficient fertilizer use is key to optimizing productivity and reducing nutrient losses that can be detrimental for the environment, such as nitrous oxide (N2 O) emissions. Because microbial communities regulate nitrogen (N) fate in soils, some agrochemicals inhibit specific transformations to reduce N losses. Our study aimed to describe short-term dynamics of N-cycling genes and transcripts and N2 O emissions after fertilization with urea-ammonium nitrate (UAN) with or without the addition of nitrification plus urease inhibitors (NUI). The experiment consisted of 4-ha corn plots located in SE Ontario, Canada, where field-scale N2 O emissions were monitored continuously using micro-meteorological techniques. Soil samples (0–10 cm) were taken 10 days before (baseline) and 2, 6, 9, 13 and 16 days after fertilization, and immediately flash-frozen. We co-extracted DNA and RNA and, using real-time PCR, quantified genes/transcripts targeting total bacteria (16S rRNA) and key N-cycling groups: ureolytic ( ureC ), ammonia-oxidizers (bacterial/archaeal amoA ), nitrite-reducers ( nirK / nirS ) and N2 O-reducers (clade I/II nosZ ). The addition of NUI did not prevent an N2 O flux event but reduced its duration and magnitude by more than 50%, and net cumulative N2 O emissions for the sampling period by ~68%. NUI effects on N-cycling microorganisms were evident on day 9, as a transient reduction (40–56%) of ammonia-oxidizers and denitrifiers. Changes in transcripts were minor and only detectable on ureC (day 2), nirS and clade II nosZ (day 9). NUI did not interfere with temporal fluctuations in nirK and nirS, but it differentially affected nosZ response to a later rainfall event. Unexpectedly, N2 O emissions were negatively associated with the ratio between nitrite-reducers and N2 O-reducers. NUI effects on N-cycling microorganisms were minor and transient but resulted in a field-scale reduction in N2 O emissions, possibly due to a combination of environmental factors and legacy effects from previous years of treatment. Highlights: Nitrification and urease inhibitors affected N-cycling genes/transcripts. This effect was small and transient, mostly on denitrifiers and nitrifiers. Inhibitors reduced the initial N2 O peak and cumulative N2 O emissions. Inhibitors affected N2 O emissions earlier than N-cycling genes/transcripts. N2 O emissions were lower when nitrite-reducers were more abundant than N2 O-reducers.